Aikido paso a paso: una guía práctica - Nalda Albiac, José Santos (Revista de Artes Marciales Asiáticas, 2012)
Moriteru Ueshiba. Barcelona: Kairos, 2009. 197 páginas. 18x24 cm. I.S.B.N.: 978-84-7245-699-0.